A rare case of orbital myositis - Yawar, Belqees; Malik, Zainab; Naz, Faiza (Journal of Ayub Medical College Abbottabad, 2021)
The orbital myositis is a rare inflammatory disorder of extraocular muscles and is considered a subtype of nonspecific orbital inflammatory syndrome. It is usually a unilateral disease process with a limited course. We report a case of a 34-year-old man who was referred to the Radiology Department at Shifa International Hospital, Islamabad with 6 months history of severe pain, swelling, and redness in the left eye associated with blurring of vision and headache. Initially, the patient had contrast enhanced CT scan orbits which showed asymmetrically thickened, minimally enhancing left optic nerve having indistinct margins with thickened superior rectus and superior oblique muscles, indistinct superior ophthalmic vein, soft tissue nodularity in the medial intraconal space fat, and slight left exophthalmos. Differentials of orbital pseudo tumour and lymphoma were given. Further evaluation by post contrast MRI with orbits protocol was suggested which showed proptosis, the significant infiltrative disease in the superomedial aspect of left orbit involving the adjacent fat with thickening, enlargement, and heterogeneous enhancement of the superior rectus, medial rectus, and superior oblique muscles with relatively lesser degree involvement of their tendons. The infiltrative thickening also involved the optic nerve sheath and seen invading the optic nerve at the orbital apex. On basis of the imaging features and clinical picture, a diagnosis of orbital myositis with optic neuropathy was given. The patient was given corticosteroids and showed rapid symptomatic improvement. Keywords: Orbital myositis; inflammatory disorder; extra-ocular muscles; contrast enhanced MRI orbit; corticosteroids